Analyzing the mechanism of strategic orientation towards digitization and organizational performance settings enduring employee resistance to innovation and performance capabilities - Wang, Yurong (Frontiers in Psychology, 2022)
Resistance to innovation is a behavioral barrier to implementing innovation in any organization. It is associated with employees' demotivation to adopt new technologies. Strategic orientation toward digitalization is a new dimension in shaping innovative organizational performance. It is also evident from past studies that certain employees' capabilities are associated with organizations' strategic orientation when undergoing digitalization. This study evaluates the association of these factors for attaining innovative organizational performance. Firstly, it evaluates the relationship of strategic orientation towards digitalization with digital capabilities, i.e., digital knowledge and innovation. This study also explores the role of capabilities between strategic orientation towards digitalization and innovative organizational performance. Moreover, the negatively regulating role of resistance to innovation as a moderator is also tested between capabilities and innovative organizational performance in this research. In their research, the authors discovered a connection between strategic orientation towards digitalization and innovative organizational performance. The findings of the study also show that digital knowledge capability and innovation capability have a substantial impact on innovative organizational performance. The research also discovered that employees' resistance to innovation exerts a sizeable moderating influence on the connection between digital knowledge competence and innovation capability inside the innovative organizational performance. According to the study's findings, strategic orientation towards digitalization is vital for enhancing the innovation power of businesses and their digital knowledge competency, both of which are essential for the development of the entrepreneurial system. The model that has been proposed is available to entrepreneurs so that they can apply it in their businesses to advance the entrepreneurial system appropriately. The authors present a theoretical model for entrepreneurial systems based on the strategic orientation towards the digitalization approach. This model is something that entrepreneurs could utilize to improve the performance of their organizations as a whole. In addition, the employee's resistance to innovation is used as a moderator in the model, which is another innovative method. The research contributes new and essential information to the existing literature on innovative organizational performance.